Effects of Lemuru fish oil and palm oil flushing on intake, rumen fermentation, and apparent digestibility in gestating Garut ewes - Nurlatifah, Aeni; Khotijah, Lilis; Arifiantini, Raden Iis; Maidin, Mashitah Shikh; Kustantinah, K.; Zulfa, Insani Hubi; Diansyah, Athhar Manabi; Astuti, Dewi Apri; Herdis, Herdis; Sitaresmi, Pradita Iustitia (ResearchersLinks Ltd, 2025)
Flush feeding is nutritional strategy design to enhance nutrient quality of diet in short-term period during critical reproductive phase. This study evaluated effect of a flushing diets with lemuru fish oil, palm oil, and their combination on nutrient digestibility and growth performance response in gestating Garut ewes. Twenty ewes were randomly assigned to four idetary treatments; C = control diet PO = palm oil enriched + flushing diet; PFO = lemuru fish and palm oil + flushing diet; FO = Lemuru fish oil enriched + flushing diet. Flushing was applied for two weeks before and after mating, and resume two weeks prior to parturition through two weeks post partum. Outside that period, all ewes were fed with control diet. Feeding consumption and ADG were recorded during gestation. Fermentability and digestibility were observed during flushing period. The results showed that there was no difference (P>0.05) in dry matter intake among all treatments, although fat intake was significantly greater in PO compared to other treatment (P<0.05). Dry matter digestibility and organic matter digestibility were significantly improved in PO group (82.61%) compared to C (76.62%). Protein and fat digestibility also improved significantly (P<0.05) in oil-suplemented group compared to the control group. However, rumen fermentability, blood metabolites, body conditioning score (BCS), average daily gain (ADG), and feed efficiency (FE) were not signifficantly affected by oil supplementation. Inclusion of up to 4.2% palm oil, lemuru fish oil, or their combination in flushing diets improved apparent nutrient digestibility without impairing rumen fermentation or maternal performance, indicating a safe and efficient metabolic adaptation. Although the short-term maternal growth responses were not significant, these findings provide valuable insight for optimizing dietary energy strategies in future applications.